Alpha-Fetoprotein for Prediction of Placenta Accreta in Women with Complete Placenta Previa Centeralis: A Prospective Study (Indian Journal of Public Health Research & Development, 2020)
Background: Placenta accreta (PA) is a major life-threating obstetrical burden associated with high morbidityand mortality. This study aims to evaluate the ability of alpha-fetoprotein for prediction of placenta accretain women with complete placenta previa centeralis.Method: This is a prospective study carried out at Minia Maternity University Hospital, Egypt during theperiod from October 2017 to March 2019. This study included a total of 100 pregnant women who areadmitted to the hospital for CS between 28:38 weeks of gestation. They were classified into 2 groups (50women per each), group (I) Diffuse PA: include women with diffuse placenta accreta and group (II) Controlgroup: include women with normally implanted placenta.Results: Both groups were comparable regarding age, residence and parity however, diffuse PA group hadsignificantly higher number of cases with ? 4 previous CSs and positive history of placenta previa. Group(I) had lower postoperative heamoglobin and platelet count (p
Keywords: Alpha-fetoprotein, Prediction, Placenta accreta, Placenta previa, Prospective Study